2000
DOI: 10.1088/0954-0083/12/4/311
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Segmented Polyurethanes Containing Polyhedral Oligomeric Silsesquioxanes Nanostructured Molecules

Abstract: Segmented polyurethanes based on diphenylmethane-4,4 -diisocyanate and polytetramethylene glycol were synthesized using a mixture of polyhedral oligomeric silsesquioxane (POSS)-diol and 1,4-butanediol as chain extenders. The polymers were characterized by differential scanning calorimetry, wide-angle x-ray diffraction (WAXD), small-angle x-ray scattering (SAXS) and tensile property tests. Microphase separation between the hard and soft segment domains was observed in all the samples by SAXS. The increase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
90
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 9 publications
12
90
4
Order By: Relevance
“…The POSS molecules have been successfully incorporated into many polymers, such as styryls, acrylics, liquid-crystalline polyesters, siloxanes, and polyamides. [22][23][24][25][26][27][28][29][30][31] Either by chemical or physical means, the POSS molecules can be dispersed in the polymer matrix by the adjustment of the chemical groups attached to the silicon atoms. The addition of POSS molecules can enhance many properties, such as heat resistance, oxygen permeation, and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The POSS molecules have been successfully incorporated into many polymers, such as styryls, acrylics, liquid-crystalline polyesters, siloxanes, and polyamides. [22][23][24][25][26][27][28][29][30][31] Either by chemical or physical means, the POSS molecules can be dispersed in the polymer matrix by the adjustment of the chemical groups attached to the silicon atoms. The addition of POSS molecules can enhance many properties, such as heat resistance, oxygen permeation, and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, functionalized POSS, usually containing one or more OH groups participate in the reaction and form urethane bonds with diisocyanates leading to often complex architectures which we are going to describe in the following. The reaction may take place in the presence of small amounts of a suitable solvent such as tetrahydrofuran (THF) [30], N,N-dimethylformamide (DMF) [31], methyl ethyl ketone (MEK) [32], dimethylacetamide (DMAC) The influence of POSS nanoparticles on selected thermal properties of polyurethane-based hybrids 291 [33] or even in solvent-free environments [34,35] in which case the polyol dissolves the other components (diisocyanate and POSS). The selection of the solvent is obviously crucial for the effective reaction and good dispersion of the POSS moieties.…”
Section: Polyurethane/poss Nanocompositessynthesis and Processingmentioning
confidence: 99%
“…Crystal size of the copolymers in the 101 direction can be estimated by the Scherrer formula (equation 11) analyzing the most intense reflection at 2θ=7.2° L = (k Îť)/(β hkl cosθ) (11) where β hkl is the half-height width of the hkl indexed reflection, θ = diffraction angle, Îť = wavelength of radiation source, and k is a constant close to unity. Results concerning high POSS level powders are reported in Table 5 for both copolymer series.…”
Section: Fig 5 X-ray Diffraction Profiles Of Bu-poss Copolymer Filmmentioning
confidence: 99%
“…For example, it has been reported that introduction of POSS in an inherently amorphous architecture, like a methacrylic random copolymer, completely suppresses its crystallization behaviour [8]. By contrast, in other cases, ordered, self-assembled hybrid structures were found in polystyrene [9], polynorbornene [10], polyurethanes [11], polybutadiene [12] and even when host matrices were crystallizable like in case of polyethylene [13,14]. The nature of the obtained nanostructure, whether amorphous or crystalline, has a significant effect also on physical properties of the hybrid material like its stiffness or thermal stability.…”
Section: Introductionmentioning
confidence: 99%